Serum paracetamol-protein adducts in ambulatory subjects: Relationship to recent reported paracetamol use. (3rd April 2018) - Heard, Kennon; Anderson, Victoria E.; Lavonas, Eric J.; Dart, Richard C.; Green, Jody L.
Abstract: Context: Serum paracetamol-protein adducts (PPAs) are a novel potential biomarker of paracetamol exposure. The relationship between serum PPA concentrations and reported paracetamol use in ambulatory adults has not been previously described. Materials and methods: This was a cross-sectional study of ambulatory adults. A detailed medication history was obtained from all subjects and subjects were stratified by reported paracetamol use in the 2 weeks prior to enrolment. Serum PPAs were measured in all subjects and correlated with reported dose, time of last ingestion and demographics. Results: We enrolled 230 in the paracetamol exposure arm and 74 in the no exposure arm. 98/230 (42.6%)of subjects who reported paracetamol exposure had PPA detected and 68/74 (91.9%) of subjects who denied paracetamol exposure had no PPA detected. PPA concentrations were positively correlated with total paracetamol dose and with more recent ingestion. Discussion: Detection of serum PPA generally reflects paracetamol exposure histories in ambulatory adults. Concentrations are well correlated with reported dose and time from last dose. Conclusions: Serum PPA can be detected with reported therapeutic use of paracetamol but may not be detected in all patients who report taking paracetamol.